Use of thermobalancing therapy in ageing male with benign prostatic hyperplasia with a focus on etiology and pathophysiology. (2nd January 2017) - Allen, Simon; Aghajanyan, Ivan
Abstract: Introduction : We investigated if "thermobalancing" therapy (TT), using Dr Allen's therapeutic device (DATD) in men with benign prostatic hyperplasia (BPH), can aid in understanding the etiology and pathophysiology of BPH. Methods : We compared urinary and other parameters of BPH patients who received TT over 6 months (treatment group) with those of healthy volunteers who had not received the treatment (control group). Dynamics of symptoms and indicators in each group were evaluated in comparison with their data at the beginning and end of the study. Parameters were the International Prostate Symptom Score (IPSS) for urinary symptoms and quality of life (QoL), ultrasound measurement of prostate volume (PV) and uroflowmetry (maximum flow rate, Q max ). TT effectiveness was examined in 124 men with BPH and PV <60 mL. We also investigated the data of five patients with BPH and PV >60 mL. Results : TT decreased urinary symptoms and PV, increased Q max and improved QoL in men with BPH, PV <60 mL, and in men with BPH, PV >60 mL. Conclusions : The present study demonstrated that TT is effective for BPH, suggesting that blood circulation plays a crucial role in its cause. The continuous heat exposure that does not exceed the normal body temperature terminates the trigger of BPH development, "micro-focus" of hypothermia, and the following spontaneous expansion of capillaries. TT could be considered to be a useful tool in BPH treatment.